2021
DOI: 10.3390/ijms222413676
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed SiOC(N) Ceramic Scaffolds for Bone Tissue Regeneration: Improved Osteogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells

Abstract: Bone tissue engineering has developed significantly in recent years as there has been increasing demand for bone substitutes due to trauma, cancer, arthritis, and infections. The scaffolds for bone regeneration need to be mechanically stable and have a 3D architecture with interconnected pores. With the advances in additive manufacturing technology, these requirements can be fulfilled by 3D printing scaffolds with controlled geometry and porosity using a low-cost multistep process. The scaffolds, however, must… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…10,11 In recent years, various materials have been widely applied to prepare 3D porous scaffolds, including natural polymers like gelatin, 12 silk fibroin, 13 and alginate, 14 as well as synthetic polymers like polylactic acid, 15 poly(e-caprolactone), 16 poly-(lactic-co-glycolic acid), 17 and other inorganic materials like ceramics. 18 Among them, silk fibroin, a natural protein derived from Bombyx mori silkworm with abundant supply, has gained wide attention owing to its excellent biocompatibility, controllable biodegradation, tunable mechanical properties, and versatile processability. [19][20][21] Much encouraging work concerning porous silk fibroin scaffolds has been reported using different fabrication techniques such as freeze drying, 22,23 gas foaming, 24,25 and salt leaching.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In recent years, various materials have been widely applied to prepare 3D porous scaffolds, including natural polymers like gelatin, 12 silk fibroin, 13 and alginate, 14 as well as synthetic polymers like polylactic acid, 15 poly(e-caprolactone), 16 poly-(lactic-co-glycolic acid), 17 and other inorganic materials like ceramics. 18 Among them, silk fibroin, a natural protein derived from Bombyx mori silkworm with abundant supply, has gained wide attention owing to its excellent biocompatibility, controllable biodegradation, tunable mechanical properties, and versatile processability. [19][20][21] Much encouraging work concerning porous silk fibroin scaffolds has been reported using different fabrication techniques such as freeze drying, 22,23 gas foaming, 24,25 and salt leaching.…”
Section: Introductionmentioning
confidence: 99%
“…Vitality assay was only performed in a qualitative way, similar to other authors [ 32 , 68 , 71 ], to acquire not only a direct answer regarding cell vitality after culturing, but also to visualize and localize exactly which cells are still alive. Hence, so far no qualitative vitality analysis, such as the Presto Blue Assay [ 33 ], the ((3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) Assay [ 77 ] or the fluorescent Alamar Blue Assay, was included, which will be performed in future. Bone-marrow-derived MSCs were chosen for this study due to their easy access and their well-established higher osteogenic and chondrogenic differentiation capacities in contrast to adipose-tissue-derived stem cells [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technique is mainly used to extrude solid or slurry materials in 2D planes according to a specific scanning path and form a planar structure with pore morphology. It is followed by superimposing multiple planar structures with a certain thickness in the Z axis sequentially to finally build pore structures of porous materials ( Cubo-Mateo and Rodriguez-Lorenzo, 2020 ; Sakthiabirami et al, 2021 ; Yang et al, 2021 ; Kilian et al, 2022 ). Considering this molding technology’s characteristics, the prepared material’s structure in the 2D plane can be controlled.…”
Section: Definition Of Pore Structure Dimensionmentioning
confidence: 99%
“…This size determines whether the cells can successfully enter the interior portion of the porous scaffold to perform their actual function ( Deb et al, 2018 ). When the pore structure and pore throat size meet the above requirements, studies have shown that the smaller the pore throat size, the better the cell adhesion, proliferation, and differentiation for bone formation, as shown in Figure 4C ( Yang et al, 2021 ). The main reason is that since the pore throat size reflects the angle, distance, and curvature between rods or walls in the pore structure, the specific mechanism by which the pore throat size causes differences in the cellular state may be related to differences in intracellular stress stimulation due to the morphology of cell adhesion and growth ( Bershadsky et al, 2003 ; Rumpler et al, 2008 ; Bidan et al, 2013 ).…”
Section: Significance Of Pore Structure Dimensionmentioning
confidence: 99%
See 1 more Smart Citation